PENGARUH ELECTRONIC WORD OF MOUTH, ONLINE CONSUMER REVIEW, DAN INTEGRATED MARKETING COMMUNICATION DI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA KONSUMEN GHEALSHY SHOES) - riris eka atsila; Siti Saroh; dadang krisdianto (LPPM FIA Unisma Malang, 2020)
The intense competition in the telecommunications business at this time, the company implemented a variety of strategic steps to maintain the existence of consumers in using a product. This research was conducted to examine the effect of Electronic Word of Mouth, Online Consumer Review, and Integrated Marketing Communication on social media on purchasing decisions on consumers of Ghealshy Shoes. The location of this research is for some consumers who have been shopping at Ghealshy Shoes by using quantitative descriptive methods with a total sample of 150 respondents and using multiple linear regression analysis techniques